Extracellular Alkaline pH Leads to Increased Metastatic Potential of Estrogen Receptor Silenced Endocrine Resistant Breast Cancer Cells - Khajah, Maitham A. (Public Library of Science, 2013)
INTRODUCTION: Endocrine resistance in breast cancer is associated with enhanced metastatic potential and poor clinical outcome, presenting a significant therapeutic challenge. We have established several endocrine insensitive breast cancer lines by shRNA induced depletion of estrogen receptor (ER) by transfection of MCF-7 cells which all exhibit enhanced expression profile of mesenchymal markers with reduction of epithelial markers, indicating an epithelial to mesenchymal transition. In this study we describe their behaviour in response to change in extracellular pH, an important factor controlling cell motility and metastasis. METHODS: Morphological changes associated with cell exposure to extracellular alkaline pH were assessed by live cell microscopy and the effect of various ion pumps on this behavior was investigated by pretreatment with chemical inhibitors. The activity and expression profile of key signaling molecules was assessed by western blotting. Cell motility and invasion were examined by scratch and under-agarose assays respectively. Total matrix metalloproteinase (MMP) activity and specifically of MMP2/9 was assessed in conditioned medium in response to brief alkaline pH exposure. RESULTS: Exposure of ER –ve but not ER +ve breast cancer cells to extracellular alkaline pH resulted in cell shrinkage and spherical appearance (termed contractolation); this was reversed by returning the pH back to 7.4. Contractolation was blocked by targeting the Na(+)/K(+) and Na(+)/H(+) pumps with specific chemical inhibitors. The activity and expression profile of key signaling molecules critical for cell adhesion were modulated by the exposure to alkaline pH. Brief exposure to alkaline pH enhanced MMP2/9 activity and the invasive potential of ER –ve cells in response to serum components and epithelial growth factor stimulation without affecting unhindered motility. CONCLUSIONS: Endocrine resistant breast cancer cells behave very differently to estrogen responsive cells in alkaline pH, with enhanced invasive potential; these studies emphasise the crucial influence of extracellular pH and caution against indiscriminate application of alkalinising drug therapy.